2007
DOI: 10.1080/01635580701586754
|View full text |Cite
|
Sign up to set email alerts
|

Retinol Increases β-Catenin-RXRα Binding Leading to the Increased Proteasomal Degradation of β-Catenin and RXRα

Abstract: Retinol utilizes a retinoid X receptor (RXR)-mediated degradation pathway to decrease beta-catenin protein in all-trans retinoic acid (ATRA)-resistant human colon cancer cells. In this study, we examined interactions between RXRalpha and beta-catenin in ATRA-resistant human colon cancer cells treated with retinol. Retinol treatment triggers relocation of beta-catenin and RXRalpha proteins. Cells treated with retinol for 8 and 24 h displayed increased cytosolic but decreased nuclear beta-catenin and RXRalpha. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
(56 reference statements)
0
16
0
1
Order By: Relevance
“…Thus, Nur77 could serve as a targeting molecule that carries its interacting proteins to certain cytoplasmic compartments for modification and degradation. Previous studies showed that RXRα, the Nur77 heterodimerization partner, could also target β-catenin for degradation through GSK3β and p53/Siah-independent mechanisms (Dillard and Lane 2007, Dillard and Lane 2008, Xiao et al 2003). Whether RXRα is involved in Nur77-mediated pathway remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Nur77 could serve as a targeting molecule that carries its interacting proteins to certain cytoplasmic compartments for modification and degradation. Previous studies showed that RXRα, the Nur77 heterodimerization partner, could also target β-catenin for degradation through GSK3β and p53/Siah-independent mechanisms (Dillard and Lane 2007, Dillard and Lane 2008, Xiao et al 2003). Whether RXRα is involved in Nur77-mediated pathway remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while it is well-established that VDR heterodimerizes with RXR to exert transcriptional effects and promote cell differentiation (40), β-catenin also acts as a transcriptional co-activator of the RXR-VDR heterodimer resulting in increased transactivation of VDRE-driven genes in the presence of 1,25(OH) 2 D 3 , and causing enhanced antiproliferation (13, 41). Moreover, RXRα , an isoform expressed in the colonic epithelium, acts via agonists that enhance the interaction between RXR and β-catenin as well as increase the degradation of β-catenin (42, 43). RXR ligands have also been demonstrated to modify the antiproliferative response of 1,25(OH) 2 D 3 in two colon cancer cell lines, exhibiting an increased proliferative response in Caco-2 cells, but blocking it in HT-29 cells (44).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, retinol treatment of colon cancer cells resulted in inhibition of cell migration and invasion [64]. Retinol also promoted proteosomal degradation of b-catenin and inhibited cell invasion by suppressing PI3K activity in colon cancer cells [65,66].…”
Section: Chemopreventive Mechanisms Of Carotenoidsmentioning
confidence: 98%
“…Reduces TNBS-induced colitis through decreasing levels of proinflammatory cytokines (TNF-a, IL-1b, and IL-17) in mice [63] Retinol Inhibits cell migration and invasion through decreasing gene expression and activities of MMPs [64] Decreases nuclear level and promotes proteosomal degradation of b-catenin [66] Inhibits cell invasion by suppression of PI3K activity [65] DHA Induces apoptosis, cell-cycle arrest and decreases colon cancer cell growth independent of p53 status [68] Suppresses arachidonic acid-induced cell proliferation, PGE 2 production, and COX-2 expression [69] Induces proteasome-dependent degradation of b-catenin and decreases its downstream gene MMP-7 and VEGF [70] Induces apoptosis through downregulation of Akt signaling [71] Conjugated linoleic acid Inhibits colon cancer growth through reducing phosphorylation of ERK1/2 and downstream c-myc [72] Decreases mRNA expression of TNF-a, IL-6, and IL-12 in human colonic epithelial Caco-2 cells [73] ERK1/2, extracellular signal-regulated protein kinase.…”
Section: All-trans-retinoic Acidmentioning
confidence: 99%